ANALISA PERILAKU KONSUMEN TERHADAP MERK DAN HARGA MAKANAN RINGAN (SNACK) - Susanti Wahyuningsih (STIE Pelita Nusantara Semarang, 2007)
This research about brand and price of snacks consumen’s attitude at student at SMK Pelita Nusantara 1 Semarang. Research problem will be discussed are (1) How for worker brand to the consumen’s attitude, (2) How for worker price to the consumen’s attitude, and (3) 3. How for worker brand and price to consumen’s attitude.The research used dobled regression analisis and determination koefisien, and then (1) Variable brand as independent variable and consumen’s attitude as variable dependent, (2) Variable price as independent variable, consumen’s attitude as variable dependent, and (3) Variable brand and price as independent variable and consumen’s attitude as variable dependent. Total sample is taken 80 responden used random sampling by questioner.